MENENTUKAN KUANTITAS DAN KOMPONEN LEUKOSIT MENCIT (Mus musculus) PADA TITIK TERENDAH PASCA RADIASI GAMMA CO-60 - Ayu Asari Dewi, Ni Kadek; Sutapa, Gusti Ngurah; Balik Sudarsana, I Wayan (BULETIN FISIKA, 2013)
Research has been conducted to determine the lowest point of the quantity and types leukocytes of mice after Co-60 gamma radiation. Number of male mice were used as much as 20 at 35 days of age were using panoramic batch irradiators (IRPASENA) gamma radiation facility at the Centre for Isotope and Radiation Applications (BATAN) by a dose of 1 Gy, 2 Gy, 3 Gy and then observed quantity and types leukocytes of mice every 10 days for 2 months. Obtained from this study the lowest point of the quantity and leukocytes component occured on day 30 approaching day 50. After the 30th day which is day 40 and 50 there was an increase although not significant, 60th day of observation while showed a significant increase.